1997
DOI: 10.1002/(sici)1097-0029(19970201)36:3<201::aid-jemt8>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Round window membrane. Structure function and permeability: A review

Abstract: The ultrastructure of the round window membrane of humans, monkeys, felines, and rodents discloses three basic layers: an outer epithelium, a middle core of connective tissue, and an inner epithelium. Interspecies variations are mainly in terms of thickness, being thinnest in rodents and thicker in humans. Morphologic evidence suggests that the layers of the round window participate in absorption and secretion of substances to and from the inner ear, and that the entire membrane could play a role in the defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 33 publications
0
82
0
Order By: Relevance
“…The role of RWM is to release mechanical energy and/or conduct sound vibration to the scala tympani of the cochlea (Wever and Lawrence, 1948;Goycoolea and Lundman, 1997). The compliance of RWM affects its ability to be displaced by, or to displace, cochlear perilymph.…”
Section: Introductionmentioning
confidence: 99%
“…The role of RWM is to release mechanical energy and/or conduct sound vibration to the scala tympani of the cochlea (Wever and Lawrence, 1948;Goycoolea and Lundman, 1997). The compliance of RWM affects its ability to be displaced by, or to displace, cochlear perilymph.…”
Section: Introductionmentioning
confidence: 99%
“…20 --22,16 --18 The structure of the outer epithelium is such that substances can pass from the middle to the inner ear by selective absorption and secretion. 23 The factors influencing permeability through the RWM include the molecular weight and configuration of the protein, its contact time and the concentration of the substances in the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…where, h from Equation (33) is the thickness of RWM, which is approximately 10 mm in the guinea pig (Goycoolea & Lundman, 1997).…”
Section: Establishing the K P Numerical Equationmentioning
confidence: 99%
“…It consists of three basic layers: an outer epithelium layer, a middle core of connective tissue, and an inner epithelium (Hellstrom et al, 1989). Animal studies have shown that this triple-layered membrane absorbs or secretes substances in the inner ear, which makes it the main portal for drug delivery to the inner ear (Juhn et al, 1989;Goycoolea & Lundman, 1997). For further development and translation of this promising therapeutic strategy to controlled clinical trials, it is necessary to conduct preclinical studies to establish pharmacokinetic and toxicological dose-effect relationships.…”
Section: Introductionmentioning
confidence: 99%